Analysis of Characteristics of Mocaf (Modified Cassava Flour) with Variations of Fermentation Time and Bread Yeast Concentration (Saccharomyces cerevisiae) - Afifah Lis Apriliani; Abdul Haris Mulyadi (Universitas Muhammadiyah Purwokerto, 2022)
Cassava is a local food that produces carbohydrates. Cassava can be processed and has great potential to be processed into various kinds of food products, such as Mocaf. Mocaf is cassava flour made by fermentation, with the principle of modification of cassava cells, this modification can change the characteristics of flour both chemically and physically. Mocaf can be used as a substitute for wheat flour. In this study, the manufacture of mocaf was carried out by fermentation using variations in the length of fermentation time and also the amount of concentration of baker's yeast (Saccharomyces cerevisiae). The time used for fermentation used in this study was 1; 1.5; 2; 2.5; and 3 days. While the amount of yeast used is 2.5; 5; 7.5; 10 and 12.5 grams. The results of this study, especially on yield, are very influential, the longer the fermentation time and the higher the amount of yeast concentration, each of which will produce less % yield. While the analysis of characteristics such as water content, ash content, fiber content, acid degree, HCN content and also color analysis have all met SNI.